Prospective study on biochemical markers causing recurrent miscarriages in Iraqi women of reproductive age - Ruqaya Kahtan Abbas,; Amani Jasim,; Qater Al Nada Ali Kanaem AL Ibady, (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the levels of elemental calcium, vitamin D3, malondialdehyde and super oxide dismutase enzymes in serum of women having recurrent miscarriages with normal healthy pregnant women. Method: The prospective study was conducted at Al-Karkh Maternity Hospital, Baghdad, Iraq, and Al-Alawia Maternity Hospital, Baghdad, Iraq, from February to August 2022, and comprised adult pregnant women having recurrent miscarriages without being hypertensive or diabetic in group A and normal healthy pregnant women in control group B. Blood samples were obtained from all the subjects. Besides, placental tissues were obtained from some members from both the groups. Levels of elemental calcium, vitamin D3, malondialdehyde and superoxide dismutase enzymes in serum were evaluated and compared between the groups. Malondialdehyde and super oxide dismutase enzymes in the placental tissues were also compared. Data was analysed using SPSS 20. Results: Of the 140 women, 70(50%) were in each of the 2 groups. The overall age range of the sample was 18-43 years. Placental tissues were obtained from 40(57.14%) in group A and 30(42.85%) in group B. In group A, miscarriage was reported in the first trimester in 45(62.3%) cases, 21(30%) in the second trimester and 4(5.7%) in the third trimester. Mean level of serum elemental calcium, vitamin D3, malondialdehyde and super oxide dismutase were significantly different between the groups (p<0.05), and the same was the case with the placental tissues (p<0.05). Conclusion: The causes of recurrent miscarriage in women could be attributed to changes in the levels of elemental calcium, vitamin D3, super oxide dismutase and malondialdehyde in serum and placental tissues. Keywords: Pregnancy, Abortion, Spontaneous, Malondialdehyde, Cholecalciferol, Placenta, Vitamins, Oxides.